2005
DOI: 10.1176/appi.ajp.162.9.1644
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Social Cognition and Response Flexibility in Pediatric Bipolar Disorder

Abstract: Findings of impaired social cognition and response flexibility in youths with pediatric bipolar disorder suggest continuity between pediatric bipolar disorder and adult bipolar disorder. These findings provide a foundation for neurocognitive research designed to identify the neural mechanisms underlying these deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
175
4
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 196 publications
(199 citation statements)
references
References 51 publications
(78 reference statements)
15
175
4
5
Order By: Relevance
“…This supports findings of impaired social cognition and response flexibility in euthymic adolescents with bipolar disorder [53]. Another study showed increased subcortical activity to positive stimuli but increased DLPFC activity to negative stimuli in adolescents with bipolar disorder [52].…”
Section: Pediatric Bipolar Disordersupporting
confidence: 81%
“…This supports findings of impaired social cognition and response flexibility in euthymic adolescents with bipolar disorder [53]. Another study showed increased subcortical activity to positive stimuli but increased DLPFC activity to negative stimuli in adolescents with bipolar disorder [52].…”
Section: Pediatric Bipolar Disordersupporting
confidence: 81%
“…BD children and adolescents demonstrate deficits in executive function 206 and emotion processing, 207 and impaired social cognition and response flexibility. 208 As with adult BD, it has been proposed, therefore, that pediatric BD may be associated with functional abnormalities in neural systems supporting emotion regulation processes. 209,210 There are several findings that support this.…”
Section: Pediatric Bipolar Disorder and High-risk Populationsmentioning
confidence: 99%
“…These psychological processes are of interest because children with BD have difficulty categorizing facial emotions (27) and regulating both their attention (28) and their affect (29). These deficits may be related: children with BD may mislabel facial emotions because their affective response to a face disrupts emotion categorization; such mislabeling may contribute to inappropriate emotional responses to environmental stimuli, and thus to emotional dysregulation.…”
mentioning
confidence: 99%